2022
DOI: 10.3399/bjgp.2021.0345
|View full text |Cite
|
Sign up to set email alerts
|

Emotional distress, anxiety, and depression in South Asians with long-term conditions: a qualitative systematic review

Abstract: People with physical-mental comorbidity have a poorer quality of life, worse clinical outcomes and increased mortality compared to people with physical conditions alone. South Asians (SAs) are the largest minority group in the UK and are more likely to have long-term conditions (LTCs) such as diabetes and heart disease. SAs are less likely to recognise symptoms which may represent mental health problems. To explore how people of SA origin with LTCs understand, experience and seek help for emotional distress, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Psychosocially, attribution, cognition and perception of disease, doctor-patient relationship, and coping strategies all affect one’s help-seeking behavior. Patients’ attribution and cognition of symptoms or diseases often affect their help-seeking behavior ( 21 , 22 ). Some of the patients in our study attributed depression either to difficulties in T2DM management, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychosocially, attribution, cognition and perception of disease, doctor-patient relationship, and coping strategies all affect one’s help-seeking behavior. Patients’ attribution and cognition of symptoms or diseases often affect their help-seeking behavior ( 21 , 22 ). Some of the patients in our study attributed depression either to difficulties in T2DM management, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analytic review suggested that as individuals in Asia or with Asian origins may be affected by collectivistic cultural orientation, they tend to deal with difficulties first within a core unit such as family ( 31 ), rather than reaching out for other resources. It was also suggested that treatment-seeking was associated with perceived failure of coping strategies ( 21 ). Some participants in our study expressed a preference for self-help, which could be interpreted as the need for autonomy and self-esteem.…”
Section: Discussionmentioning
confidence: 99%
“…Further insights into the mental health burden in people with axial SpA can be gleaned from qualitative research that captures affective experience [ 7 , 8 ]. Affective experience includes emotions and moods, which differ in duration and specificity but share dimensions of valence, motivation and arousal [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, to our knowledge, only one self‐harm study included British South Asian men adolescents (Klineberg et al, 2013). A recent systematic review has also illustrated a dearth of research on emotional distress and help‐seeking behaviour in South Asian men (Awan et al, 2022). In addition, despite the requirement for culturally sensitive treatments, there have been no studies on culturally adapted self‐harm interventions for South Asians in the UK.…”
Section: Introductionmentioning
confidence: 99%